ANALISIS KEPUASAN KONSUMEN DITINJAU DARI KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN PADA KAFE GRIYO NGANJUK - Sari, Nindy Kurnia; Aliami, Sri; Leksono, Poniran Yudho (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The research is motivated by the effort to fulfill culinary beverage needs, particularly in the form of coffee. Consumers expect to get products of good quality that match their taste preferences at an affordable price, accompanied by excellent service to achieve satisfaction. On the other hand, companies strive to design and implement appropriate strategies, especially related to the marketing mix and service concepts, to win the competition, particularly in the cafe business. This research aims to analyze the significant relationship between product quality and price, separately and together, concerning consumer demand. The research adopts a quantitative and causal approach, utilizing causal techniques and data collection through questionnaires. The majority of the sample population consists of every consumer who has visited Kafe Griyo Nganjuk at least once. In total, 40 individuals responded to the survey. Multiple regression analysis was employed as the analytical method. The findings of this research demonstrate that product quality and its pricing are directly or indirectly related to consumer needs.